Perancangan Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) pada PT Famiglas Mitra Mandiri - Jesica Oktavia (Jurnal Titra, 2019)
This article PT Famiglas Mitra Mandiri is an industrial manufacturing company that work in the body construction. The company itself, produce the main body part for the heavy vehicle such as trucks or bucks. Besides, the company also produced material that related to that sector. The Owner of the company complains that they have some issues about the work accident. The work accident happens frequently almost 2-3 accident each month. As a result, the company have to pay extra money for the medical expensive. This issues is happen because, until now the company doesn’t have a management standard for health and safety. To resolved this issues, the implementation of management standard for health and safety need to be implement immediately. The data was collected using qualitive method in the company. The observation including interview, scoring and discussion with the company staff. The observation is to ensure that the company is able to use SMK3 system and to obey the legal rules by the government based on the Peraturan Pemerintah nomor 50 tahun 2012. As a result of the observation of SMK3, is it clearly to be seen that the company already fulfilled almost 72.46% (121 from 167 sub-criteria).